Percieved decision making and conflict management styles of principals and their relationship to job satisfaction of intermediate schoolteachers in Bahrain / Abdulhadi Hasan Abdulhusain Hasan Ali - Abdulhusain Hasan Ali, Abdulhadi Hasan (Institute of Graduate Studies, UiTM, 2018)
This study aimed to investigate the relationship between school principals' decision making styles, conflict management styles and personal factors, and their impact on teachers' job satisfaction at intermediate public schools in the Kingdom of Bahrain based on teachers' perception. A total of 327 forms out of 2197 teacher population has been returned and considered useable for data analysis. Data for the research were collected through questionnaires and interviews. All the rating scales had been reliability estimated at Cronbach's Coefficient Alpha of above .70.Overall, the degree of job satisfaction as reported by intermediate public school teachers in Bahrain was moderate. The findings highlighted there was more influence of intrinsic factors than extrinsic factors on job satisfaction. The findings also indicated that most school principals used compromise and collaboration styles of conflict management. In addition, the results showed that the rational decision making style was the favourite style for Principals. Regarding personal factors, the findings of this study indicated that males were more satisfied with fringe benefits and contingent rewards of job satisfaction. Also, gender has predicted the competition style as a better conflict management style. However, the current study indicated that gender has no statistically significant difference on the decision making styles of school principals. Teachers at intermediate public schools in Bahrain have been identified as moderately satisfied with their job. One of the main obstacles faced by the researcher was the absence of neutral studies on dissatisfaction factors of teachers in Bahrain. Generally, teachers were not involved in the decision making process while senior teachers were not empowered enough at intermediate level to solve conflicts. Furthermore, most teachers complained about unnecessary workload, mainly regarding marking, planning and data management in schools. In addition, some teachers in Bahrain complained of losing respect and appreciation in the local society. The study recommended that certain procedures and actions should be taken to improve job satisfaction levels of teachers. Teachers should be involved in the decision making process at schools. Besides empowering senior teachers to help resolve conflicts and support the administrators, a reform of the organisation procedures in schools is much needed to maintain a healthier working environment for teachers. Additionally, the Ministry of Education and the Ministry of Information should help teachers to maintain respect in society by launching a national campaign which enforces value and respect towards teachers.